IMPROVING THE STUDENTS’ SKILL IN WRITING DESCRIPTIVE TEXT USING ANIMATED SHORT FILM TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 6 PADANGSIDIMPUAN - Harahap, Tinur Rahmawati; Sari, Siti Meutia; Mahrani, Mahrani; Emilia, Linda (English Department, University of Riau Kepulauan, Batam,Indonesia, 2023)
From the researchers’ personal experience, writing necessitates more abilities, and some struggle to string words together to convey the meaning of what they want to say. Lack of interest due to the monotony of learning; some people, in particular,are more interested in learning through imagery rather than listening. If we educatestudents through animated films, they will be more engaged. Descriptive text isdifficult enough to learn by the students (Putri, 2019). They will try to describe manythings they find in the movie they have just watched. The researcher's aim is thatstudents can write appropriate descriptive text compositions faster than before.They can describe things more freely than usual and hope to contribute to a greaterinterest in writing. So here one of formulating of the problem in this research How far is the improvement of the students’ skill in writing descriptive textafter they are taught by using Animated Short Film? . Writing is one of the skills that must be learned and mastered. Writing is the expression of oneselfin various media through words or thoughts. (Safitri, 2019). A descriptive text attempts toprovide a detailed description of how something or someone appears (Djamdjuri &Hadi, 2021). According to (Rahmadani & Nurhaeni, 2019), Descriptive text is a type oftext seen from two sides, namely from its organizational structure and function. Anything, including items, locations, creatures, and more, can seem like this thing. Animated short films are also based on the violence ofcontextual comics. Coupled with the ability of young children to distinguish fantasyfrom good and bad reality, it can also eliminate the possibility that children willexert the attraction shown in animated short films on other people in real life. In this research, the researcher used the form of action research asstated by Wallace (1998) that is a kind of research which is done systematicallyin collecting the data on the lesson and analyzing it in order to come tosome decisions about what the future lesson should be. Using animated short film in teaching can improve the students’ skill in writing descriptive text to the eleventh grade students of SMA Negeri 6 Padangsidimpuan Padangsidimpuan in 2022 - 2023 academic year. It can be seen from the value of students mean score of the students from 61.25 become 80.79